Treatment of fish-processing wastewater by co-culture of Candida rugopelliculosa and Brachionus plicatilis - Lim, J; Kim, T; Hwang, S (Water Research, 2003)
This research was conducted as a part of the continuous development of a novel technique for managing fish-processing wastewater by cultivating proteolytic yeast, Candida rugopelliculosa, as possible diet of the rotifer, Brachionus plicatilis. It was feasible to use Alaska Pollack processing wastewater as a growth medium for C rugopelliculosa, which was stimulatory for growth of the rotifer by 18.3% over the commercial diet of Saccharomyces cerevisiae. Maximum growth of C rugopelliculosa and reduction of influent soluble chemical oxygen demand (SCOD) concentration were respectively (6.09+/-0.04) x 10(6) cells/ml and 70.0% at 6.3 h hydraulic retention time (HRT). Method of 4th order Runge-Kutta approximation was successfully applied to determine the Monod kinetics of C rugopelliculosa by using unsteady state data from only one continuous unsteady state operation at a fixed HRT. The maximum microbial growth rates, mu(max), and half saturation coefficient, K-s, were determined to be 0.82 +/- 0.22 h(-1) and 690+/-220mg SCOD/L, respectively. The microbial yield coefficient, Y, and microbial decay rate coefficient, k(d), were determined to be (1.39 +/- 0.22) x 10(4) cells/mg SCOD and 0.06+/-0.01 h(-1), respectively. (C) 2003 Elsevier Science Ltd. All rights reserved. X 1 1 17 scie scopus